Pullulanase type II from a local Bacillus isolate H1.5 : isolation, production and characterization of the enzyme - Hii, Siew Ling; Ling, Tau Chuan; Mohammad, Rosfarizan; Ariff, Arbakariya (Penerbit Universiti Sains Malaysia, 2004)
Enzymes that specifically break down the branch points – debranching enzymes – have been known for more than a decade. Pullulanase (EC 3.2.1.41, pullulan 6- glucanohydrolase), which was first reported in Aerobacter aerogenes splits the α-1,6- glucosidic linkages in pullulan and give rise finally to maltotriose (Yuzuru and Masaharu, 1983). In most cases, pullulanase can also cleave the α-1,6 link of other branched polysaccharides, such as starch, glycogen and maltodextrin